Multiscale metal-based nanocomposites for bone and joint disease therapies - Yuwen Wang; Hasnain Jan; Zheng Zhong; Liangbin Zhou; Kexin Teng; Ye Chen; Jiankun Xu; Denghui Xie; Dexin Chen; Jiake Xu; Ling Qin; Rocky S. Tuan; et al. (Materials Today Bio)
Bone and joint diseases are debilitating conditions that can result in significant functional impairment or even permanent disability. Multiscale metal-based nanocomposites, which integrate hierarchical structures ranging from the nanoscale to the macroscale, have emerged as a promising solution to this challenge. These materials combine the unique properties of metal-based nanoparticles (MNPs), such as enzyme-like activities, stimuli responsiveness, and photothermal conversion, with advanced manufacturing techniques, such as 3D printing and biohybrid systems. The integration of MNPs within polymer or ceramic matrices offers a degree of control over the mechanical strength, antimicrobial efficacy, and the manner of drug delivery, whilst concomitantly promoting the processes of osteogenesis and chondrogenesis. This review highlights breakthroughs in stimulus-responsive MNPs (e.g., photo-, magnetically-, or pH-activated systems) for on-demand therapy and their integration with biocomposite hybrids containing cells or extracellular vesicles to mimic the native tissue microenvironment. The applications of these composites are extensive, ranging from bone defects, infections, tumors, to degenerative joint diseases. The review emphasizes the enhanced load-bearing capacity, bioactivity, and tissue integration that can be achieved through hierarchical designs. Notwithstanding the potential of these applications, significant barriers to progress persist, including challenges related to long-term biocompatibility, regulatory hurdles, and scalable manufacturing. Finally, we propose future directions, including machine learning-guided design and patient-specific biomanufacturing to accelerate clinical translation. Multiscale metal-based nanocomposites, which bridge nanoscale innovations with macroscale functionality, are a revolutionary force in the field of biomedical engineering, providing personalized regenerative solutions for bone and joint diseases.